Preparation method and application of acid-etched nitrogen-doped carbon nanotube wrapped elemental iron composite material
The treatment of nitrogen-doped carbon nanotubes wrapped with elemental iron material through acid etching solves the problem of stability reduction in Fe(CN) 63-consumption in microbial fuel cells, and realizes an ORR catalyst with better performance than Pt/C, with the potential to replace Pt/C.
Patent Information
- Application Number
- CN202411797735.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In existing microbial fuel cells, the consumption of Fe(CN)63- causes the stability of the reaction system to decrease, affecting battery performance, and traditional Pt/C catalysts have limited their wide application due to high cost and easy poisoning.
The nitrogen-doped carbon nanotubes are treated with acid etching to wrap the elemental iron material, dissolve the elemental iron on the surface of the catalyst, change the surface structure of the material, increase the active site of the catalyst and improve the dispersion of the active components, thereby improving the ORR performance.
It significantly improves the ORR performance and conductivity of the catalyst, can efficiently convert the chemical energy of organic matter into electrical energy, and has the potential to replace Pt/C as an ORR catalyst.
Smart Images

Figure CN119581578A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of air cathode of microbial fuel cells, and specifically relates to a preparation method and application of a composite material of elemental iron wrapped by acid-etched nitrogen-doped carbon nanotubes. Background Art
[0002] With the advancement of science and technology and the improvement of people's living standards, energy consumption has continued to rise, bringing the world the dual challenges of energy shortage and environmental pollution. As a rapidly consumed limited resource, the scarcity of fossil energy is becoming increasingly prominent, and there is an urgent need to find alternative energy sources. Microbial fuel cells (MFCs) use the catalytic effect of microorganisms and the synergistic effect of electrochemical processes to degrade organic pollutants. They can cleverly combine pollution control and energy production. They are a sustainable energy technology with broad application prospects. In microbial fuel cells, common electron acceptors such as potassium ferrocyanide and potassium dichromate can make the operating potential of the battery close to the open circuit potential due to their low cathode reduction overpotential, thereby obtaining a higher output power. However, with the increase of Fe(CN)6 3- The consumption of oxygen decreases the stability of the reaction system, affects the battery performance, and requires frequent replacement of the cathode liquid, which not only increases the operating cost but also causes secondary pollution. Therefore, finding alternative electron acceptors has become an important task. Oxygen, as an ideal electron acceptor, has become an attractive choice due to its advantages such as easy access and high standard electrode potential. The air cathode MFC uses oxygen as an electron acceptor, and its core lies in the cathode catalyst that promotes the oxygen reduction reaction (ORR). In order to achieve high current and power output of the system, it is necessary to consider how to efficiently transfer the electrons generated at the anode to the cathode. At present, Pt / C is a widely used ORR catalyst, but the high cost, scarce resources and easy poisoning of platinum limit its widespread application. Therefore, the development of low-cost and efficient ORR catalysts has become the key to research.
[0003] In recent years, carbon-based materials such as activated carbon (AC), carbon fiber, graphite, and carbon nanotubes have received extensive attention in the field of catalytic materials due to their low cost, good conductivity, large specific surface area, and high biocompatibility. In particular, carbon nanotubes, whose unique tubular structure provides abundant pores, help shorten the mass transfer distance, improve the transfer efficiency of electrons and protons, and thus improve the electrocatalytic performance. However, the ORR performance of single carbon-based materials is still far inferior to that of traditional Pt / C catalysts. To improve this situation, researchers have proposed a variety of strategies, such as heteroatom doping and construction of metal active sites, which have improved the ORR performance of carbon-based materials to a certain extent. In particular, iron-doped catalysts usually exhibit a four-electron oxygen reduction pathway, but transition metals are easy to migrate and agglomerate into particles during high-temperature pyrolysis, and the large-size cluster phenomenon has a certain inhibitory effect on the ORR performance. In response to these problems, the present invention proposes a method of treating nitrogen-doped and iron-doped carbon-based materials by acid etching, dissolving the elemental iron on the surface of the catalyst, changing the surface structure of the material, and increasing the surface active sites of the catalyst. This optimization process not only improves the coordination ability, high atomic utilization efficiency and electron transfer rate of nitrogen-doped carbon nanotubes wrapped in elemental iron, but also exhibits efficient ORR performance, making this nitrogen and iron co-doped carbon-based material likely to replace Pt / C and become a new generation of ORR catalyst. Summary of the invention
[0004] In view of the above-mentioned technical problems existing in the prior art, the purpose of the present invention is to provide a preparation method and application of an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material. The present invention promotes the formation of carbon nanotubes by adding nitrogen and iron co-doping, and alleviates the iron clustering phenomenon in the carbon nanotubes by acid etching, thereby improving the dispersibility of the active components, thereby optimizing the ORR performance and conductivity of the catalyst.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by this technology is:
[0006] A method for preparing an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material comprises the following steps:
[0007] The nitrogen-doped carbon nanotube-wrapped elemental iron material is subjected to acid etching, and then post-processed to obtain an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material; the acid is sulfuric acid, nitric acid or hydrochloric acid. The concentration of the acid is 0.1 to 1 mol / L. The elemental iron on the surface of the carbon nanotube catalyst can be dissolved by acid etching, the phenomenon of large-sized iron clusters formed by high-temperature pyrolysis can be alleviated, the surface structure of the material can be changed, the active sites of the catalyst can be increased, and the dispersibility of the active components can be improved.
[0008] The invention discloses an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron-oxygen reduction catalyst, wherein the diameter of the carbon nanotube is about 10-100 nm.
[0009] Preferably, the iron clustering phenomenon in the carbon nanotubes is alleviated by acid etching, and the iron content before acid etching is 2 to 5 times that after acid etching. That is, the weight of elemental iron in the nitrogen-doped carbon nanotube-wrapped elemental iron material and the weight of elemental iron in the acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material are (2 to 5):1.
[0010] The present invention also provides a method for preparing an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material, comprising the following steps:
[0011] (1) preparing a zeolite imidazole framework structure ZIF-8 precursor;
[0012] (2) adding an iron source and a nitrogen source to a zeolite imidazole framework structure ZIF-8 precursor to obtain a solid mixture;
[0013] (3) Pyrolyzing the solid mixture under nitrogen or inert gas protection, with a heating rate of 1 to 10°C / min, a pyrolysis temperature of 700 to 900°C, and a holding time of 2 to 3 hours, followed by cooling to obtain nitrogen-doped carbon nanotubes encapsulating elemental iron materials; by regulating the pyrolysis conditions, the zeolite imidazole framework structure ZIF-8 precursor can be induced as the basic structure, thereby causing the zeolite imidazole framework structure ZIF-8 octahedral structure to collapse, thereby promoting the formation of carbon nanotubes. Its characteristics also include: nitrogen elements are uniformly dispersed in carbon nanotubes, and elemental iron presents a large-sized cluster phenomenon.
[0014] (4) The nitrogen-doped carbon nanotube-wrapped elemental iron material is mixed with an acid for reaction, and an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material is obtained through post-treatment.
[0015] The present invention adopts zeolite imidazole framework structure ZIF-8 as a precursor, and then mixes it with dicyandiamide and ferric chloride hexahydrate and then performs ultrasonic treatment, and then centrifuges and dries the generated precipitate. The dried precipitate is subjected to high-temperature pyrolysis in a tubular furnace to form a composite catalyst of nitrogen-doped carbon nanotubes wrapped in elemental iron, and finally further treated by an acid etching step to obtain an acid-etched nitrogen-doped carbon nanotube wrapped elemental iron oxygen reduction catalyst (Fe / N-CNTs-acid). The preparation method used in the present invention alleviates the problem of large-size clusters of transition metals during high-temperature pyrolysis, that is, the surface structure of the material is changed by acid etching, the dispersibility of the active component is improved, and the material exhibits good conductivity, excellent oxygen reduction reaction (ORR) performance and its electrical generation efficiency. When applied to the MFC air cathode, the utilization efficiency of oxygen can be significantly improved. The present invention not only overcomes the limitations of traditional chemical reagents such as potassium ferrocyanide as electron acceptors, but also can efficiently convert the chemical energy of organic matter into electrical energy, and its performance is better than the existing Pt / C catalyst, and has the potential to replace Pt / C as an ORR catalyst.
[0016] In step (1), preparing a zeolite imidazole framework structure ZIF-8 precursor comprises the following steps:
[0017] Zinc nitrate hexahydrate and 2-methylimidazole are dissolved in methanol and mixed, stirred, allowed to stand, centrifuged, washed with methanol and vacuum dried to obtain a zeolite imidazole framework structure ZIF-8 precursor.
[0018] In step (2), an iron source and a nitrogen source are added to the zeolite imidazole framework structure ZIF-8 precursor, specifically comprising:
[0019] The zeolite imidazole framework structure ZIF-8 precursor obtained in step (1) is dissolved in ethanol, ferric chloride hexahydrate and dicyandiamide are added for ultrasonic treatment, and the mixture is collected by centrifugation and vacuum dried to obtain a solid mixture.
[0020] In step (4), the acid is sulfuric acid, nitric acid or hydrochloric acid; the concentration of the acid is 0.1 to 1 mol / L;
[0021] The mixing reaction time is 8 to 24 hours.
[0022] The post-treatment specifically includes: centrifugation first, washing with ethanol and deionized water alternately until neutral, and then vacuum drying.
[0023] Specifically, an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron-oxygen reduction catalyst comprises the following steps:
[0024] (1) 5-10 mmol of zinc nitrate hexahydrate and 20-40 mmol of 2-methylimidazole are dissolved in a methanol solution respectively, and then the methanol solution containing 2-methylimidazole is poured into the methanol solution containing zinc nitrate hexahydrate, and the resulting mixed solution is stirred for 10 minutes and then allowed to stand for 24 hours indoors. Thereafter, the precipitate is collected by centrifugation and washed with methanol for more than 3 times. Finally, it is dried in a vacuum oven, and the resulting material is a zeolite imidazole framework structure ZIF-8.
[0025] (2) Weigh 200-400 mg of the sample prepared in step (1) and dissolve it in an ethanol solution (solution C). Then add 10-100 mg of ferric chloride hexahydrate to the solution and ultrasonicate for 10 min. Then add 1-3 g of dicyandiamide to the solution and ultrasonicate for 20 min. Then collect the precipitate by centrifugation. Finally, vacuum dry it in an oven.
[0026] (3) The obtained solid mixture was ground with an agate mortar and evenly placed in a square porcelain boat. Then, it was placed in a tube furnace and the oxygen in the tube furnace was removed by nitrogen-vacuum cycle operation for more than 3 times. Under the protection of 50-150 mL / min nitrogen atmosphere, the temperature was increased to 700-900°C at a rate of 1-10°C / min, maintained for 2-3 hours, and then cooled to 500°C at a rate of 3°C / min, followed by a natural cooling program. The obtained sample was recorded as Fe / N-CNTs.
[0027] (4) The prepared material is added to a 0.1-1 mol / L sulfuric acid solution, stirred in a magnetic stirrer, and the acid-etched catalyst is collected by centrifugation. To remove impurities in the catalyst, the prepared catalyst is washed with ethanol and deionized water. When the pH of the supernatant is neutral, it indicates that the washing is complete. The washed catalyst is placed in an oven for vacuum drying. The prepared material is named Fe / N-CNTs-acid.
[0028] Preferably, in step (1), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:4;
[0029] Preferably, in step (2), the mass ratio of zeolite imidazole framework structure ZIF-8: ferric chloride hexahydrate: dicyandiamide is 5:1:20-30;
[0030] Preferably, in step (3), the heating rate is 5°C / min, the temperature of high-temperature pyrolysis is 800°C, and the flow rate of high-temperature pyrolysis is 100 mL / min;
[0031] Further preferably, the concentration of sulfuric acid in step (4) is 0.5 mol / L;
[0032] Further preferably, the temperature of vacuum drying in the oven is 60°C;
[0033] Preferably, the mass ratio of the iron element to the carbon element in the acid-etched nitrogen-doped carbon nanotubes encapsulating the elemental iron-oxygen reduction catalyst is m Fe :m C It is 1:20-30.
[0034] The present invention also relates to the use of the above-mentioned acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron oxygen reduction catalyst in the air cathode of a microbial fuel cell, and the catalyst can effectively improve the performance of the battery.
[0035] Compared with the prior art, the present invention has the following advantages:
[0036] The present invention uses zeolite imidazole framework structure ZIF-8 as a precursor, dicyandiamide as a nitrogen source, ferric chloride hexahydrate as an iron source, and utilizes the synergistic effect of nitrogen and iron elements to form nitrogen-doped carbon nanotubes in situ through high-temperature pyrolysis technology. Further, an acid etching process is used to reduce the iron clustering phenomenon in the carbon nanotubes and improve the dispersibility of the active components, thereby significantly improving the power generation performance of the catalyst. This improvement helps to promote the adsorption of oxygen in the air by the electrode, thereby increasing the electron transfer rate and electron utilization. The present invention also loads the catalyst on a carbon cloth diffusion electrode and applies it to the air cathode of a microbial fuel cell. The application of the catalyst can not only use oxygen in the air to replace the traditional potassium ferrocyanide electron acceptor, reduce the potential pollution of the chemical electron acceptor to the environment, but also show more excellent output power and output voltage compared to commercial Pt / C catalysts. Therefore, the catalyst of the present invention can efficiently convert the chemical energy of organic matter into electrical energy, and has great potential for replacing the existing Pt / C catalyst in the air cathode of a microbial fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of the preparation of nitrogen-doped carbon nanotube-wrapped elemental iron-oxygen reduction catalyst;
[0038] Figure 2 SEM of nitrogen-doped carbon nanotubes wrapped with pure iron air cathode;
[0039] Figure 3 This is the EDS elemental analysis of nitrogen-doped carbon nanotubes wrapped with pure iron air cathode;
[0040] Figure 4 TEM images of Fe / N-CNTs and Fe / N-CNTs-acid with a scale of 200 nm
[0041] Figure 5 TEM images of Fe / N-CNTs and Fe / N-CNTs-acid with a scale of 20 nm;
[0042] Figure 6 TEM+EDS image of Fe / N-CNTs-acid;
[0043] Figure 7 XRD patterns of Fe / N-CNTs and Fe / N-CNTs-acid;
[0044] Figure 8 This is a schematic diagram of the air cathode reaction system of a microbial fuel cell;
[0045] Fig. 9 The voltage-time curves of different air cathodes;
[0046] Fig.10 The power density and polarization curves of different air cathodes. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0048] Example 1 (for comparison): A method for preparing a nitrogen-doped carbon nanotube-wrapped elemental iron air cathode, the steps are as follows:
[0049] (1) 8 mmol of zinc nitrate hexahydrate and 32 mmol of 2-methylimidazole were dissolved in 140 and 180 mL of methanol solution, respectively. Then, the methanol solution containing 2-methylimidazole was poured into the methanol solution containing zinc nitrate hexahydrate. The resulting mixed solution was stirred for 10 min and then allowed to stand for 24 hours. The precipitate was then collected by centrifugation and washed with methanol for more than 3 times. Finally, it was dried in a vacuum oven at 60°C. The resulting material was the zeolite imidazole framework structure ZIF-8.
[0050] (2) Weigh 300 mg of the sample prepared in step (1) and dissolve it in an ethanol solution. Then add 60 mg of ferric chloride hexahydrate to the ethanol solution and ultrasonicate for 10 min. Then add 1.5 g of dicyandiamide to the solution and ultrasonicate for 20 min. Then collect the precipitate by centrifugation. Finally, vacuum dry it in an oven at 60°C.
[0051] (3) The obtained solid mixture was ground with an agate mortar, placed in a square porcelain boat, and placed in a tube furnace. The oxygen in the tube furnace was removed by nitrogen-vacuum cycle operation for more than 3 times. Under the protection of 100 mL / min nitrogen atmosphere, the temperature was increased to 800°C at a rate of 5°C / min, maintained for 2 hours, and then decreased to 500°C at a rate of 3°C / min, followed by a natural cooling program. The obtained sample was recorded as Fe / N-CNTs.
[0052] (4) Preparation of air cathode: A carbon cloth diffusion electrode was used as the current collector. 37.5 mg of Fe / N-CNTs catalyst was added to a centrifuge tube. 188 μL of nafion and 3.75 mL of isopropanol were added and ultrasonic treatment was performed for 1 hour. The solution was evenly loaded on the carbon cloth diffusion electrode by titration and finally naturally dried to prepare the Fe / N-CNTs air cathode.
[0053] The nitrogen-doped carbon nanotube-wrapped elemental iron-oxygen reduction catalyst prepared by the present invention has a preparation process Figure 1 As shown, the above catalyst is loaded on a carbon cloth diffusion electrode to prepare an air cathode. Figure 2 The SEM results show that the diameter of the carbon nanotubes is 10 to 100 nm. Figure 3 The EDS elemental analysis diagram also shows that the zeolite imidazole framework structure ZIF-8 structure is the basic structure of carbon nanotubes. With high-temperature pyrolysis, the octahedral structure of the zeolite imidazole framework structure ZIF-8 collapses, promoting the formation of carbon nanotubes. At the same time, with the collapse of the zeolite imidazole framework structure ZIF-8, the Zn element also evaporates and is discharged along with the nitrogen atmosphere.
[0054] Example 2: A method for preparing an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron air cathode, the steps are as follows:
[0055] (1) 8 mmol of zinc nitrate hexahydrate and 32 mmol of 2-methylimidazole were dissolved in 140 and 180 mL of methanol solution, respectively. Then, the methanol solution containing 2-methylimidazole was poured into the methanol solution containing zinc nitrate hexahydrate. The resulting mixed solution was stirred for 10 min and then allowed to stand for 24 hours. The precipitate was then collected by centrifugation and washed with methanol for more than 3 times. Finally, it was dried in a vacuum oven at 60°C. The resulting material was the zeolite imidazole framework structure ZIF-8.
[0056] (2) Weigh 300 mg of the sample prepared in step (1) and dissolve it in an ethanol solution. Then add 60 mg of ferric chloride hexahydrate to the ethanol solution and ultrasonicate for 10 min. Then add 1.5 g of dicyandiamide to the solution and ultrasonicate for 20 min. Then collect the precipitate by centrifugation. Finally, vacuum dry it in an oven at 60°C.
[0057] (3) The obtained solid mixture was ground with an agate mortar, placed in a square porcelain boat, and placed in a tube furnace. The oxygen in the tube furnace was removed by nitrogen-vacuum cycle operation for more than 3 times. Under the protection of 100 mL / min nitrogen atmosphere, the temperature was increased to 800°C at a rate of 5°C / min, maintained for 2 hours, and then decreased to 500°C at a rate of 3°C / min, followed by a natural cooling program. The obtained sample was recorded as Fe / N-CNTs.
[0058] (4) The prepared material was added to a 0.5 mol / L sulfuric acid solution, stirred in a magnetic stirrer for 12 hours, and the acid-etched catalyst was collected by centrifugation. In order to remove impurities in the catalyst, the prepared catalyst was washed with ethanol and deionized water. When the pH of the supernatant was neutral, it indicated that the washing was complete. The washed catalyst was placed in a 60°C oven for vacuum drying. The prepared material was named Fe / N-CNTs-acid.
[0059] (5) Preparation of air cathode: A carbon cloth diffusion electrode was used as a current collector. The Fe / N-CNTs-acid catalyst was added to a centrifuge tube, and 188 μL of nafion and 3.75 mL of isopropanol were added and ultrasonicated for 1 hour. The solution was evenly loaded on the carbon cloth diffusion electrode by titration, and finally naturally dried to prepare the Fe / N-CNTs-acid air cathode. The Pt / C air cathode was prepared in the same manner as above.
[0060] The acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron-oxygen reduction catalyst prepared in the present invention is subjected to acid etching treatment based on Example 1, and finally the acid-etched catalyst is loaded on a carbon cloth diffusion electrode to prepare an air cathode. Figure 4 and Figure 5 From the TEM images, we can see that the diameter of carbon nanotubes did not change much before and after acid etching, and the iron clustering phenomenon was significantly alleviated after acid etching. Figure 6 The TEM+EDS image can tell m Fe :m C 1:20~30. Figure 7 From the standard card of the PDF of the XRD pattern, we know that the iron element formed is mainly elemental iron. Compared with the elemental iron oxygen reduction catalyst wrapped in nitrogen-doped carbon nanotubes, the iron content of the catalyst after acid etching is significantly lower, indicating that acid etching can effectively alleviate the iron clustering phenomenon in carbon nanotubes.
[0061] Example 3: The application of nitrogen-doped carbon nanotubes wrapped with elemental iron-oxygen reduction catalysts before and after acid etching in microbial fuel cells was investigated, specifically as air cathode materials.
[0062] This embodiment adopts the air cathode prepared by the method described in Example 1 and Example 2. The MFC system is started by inoculating activated sludge. The reaction system structure is as follows Figure 8As shown. In the anode chamber of the reactor, 500 mg / L of sodium acetate is added as a carbon source. The cathode liquid uses a 50 mM phosphate buffer solution. The cathode diffusion layer is directly in contact with the air, allowing oxygen to reach the catalytic layer through the diffusion layer, thereby capturing electrons and protons to generate pollution-free water molecules. The positive and negative electrodes of the MFC are respectively installed at both ends of the cavity, and a closed circuit is formed through an external resistor.
[0063] For comparison, two comparison groups were set up in this experiment, namely carbon cloth diffusion electrode and Pt / C air cathode. The experimental groups used nitrogen-doped carbon nanotubes wrapped elemental iron air cathode (Fe / N-CNTs) and nitrogen-doped carbon nanotubes wrapped elemental iron air cathode after acid etching (Fe / N-CNTs-acid).
[0064] During the operation of the reactor, a paperless portable recorder was used to monitor the output voltage of each cycle. When the output voltage dropped below 0.05V, the solution was replaced to enter the next cycle. Fig. 9 As shown, the maximum output voltages of CC, Pt / C, Fe / N-CNTs and Fe / N-CNTs-acid are 0.236, 0.574, 0.586 and 0.592 V, respectively. It can be seen that the maximum output voltage of Fe / N-CNTs-acid is the highest, which is 2.51 times higher than that of CC. Fig.10 The power density and polarization curves of the microbial fuel cell air cathode system are shown in Figure 2. The maximum power densities of CC, Pt / C, Fe / N-CNTs and Fe / N-CNTs-acid are 173.18, 1104.35, 1195.95 and 1240.09 mW / m 2 The maximum power density of Fe / N-CNTs-acid is 1.12 times that of Pt / C, which indicates that Fe / N-CNTs-acid has the potential to replace Pt / C as an oxygen reduction reaction (ORR) catalyst.
[0065] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the protection scope of the present invention. Any changes and modifications made by any technician familiar with the technology without departing from the concept and scope of the present invention should fall within the protection scope of the present invention.
Claims
1. A method for preparing an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material, characterized in that: The following steps are involved: The nitrogen-doped carbon nanotube-wrapped elemental iron material is subjected to acid etching treatment, and then post-treated to obtain an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material, wherein the acid is sulfuric acid, nitric acid or hydrochloric acid.
2. The method for preparing the acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material according to claim 1, characterized in that: The concentration of the acid is 0.1-1 mol / L.
3. The method for preparing the composite material of elemental iron wrapped by acid-etched nitrogen-doped carbon nanotubes according to claim 1, characterized in that: The mass of elemental iron in the nitrogen-doped carbon nanotube-wrapped elemental iron material and the mass of elemental iron in the acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material are (2-5):
1.
4. A method for preparing an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material, characterized in that: The following steps are involved: (1) preparing a zeolite imidazole framework structure ZIF-8 precursor; (2) adding an iron source and a nitrogen source to a zeolite imidazole framework structure ZIF-8 precursor to obtain a solid mixture; (3) pyrolyzing the solid mixture under nitrogen or inert gas protection, with a heating rate of 1 to 10° C. / min, a pyrolysis temperature of 700 to 900° C., and a holding time of 2 to 3 hours, and then cooling to obtain a nitrogen-doped carbon nanotube-wrapped elemental iron material; (4) The nitrogen-doped carbon nanotube-wrapped elemental iron material is mixed with an acid for reaction, and an acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material is obtained through post-treatment.
5. The method for preparing the acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material according to claim 4, characterized in that: In step (1), preparing a zeolite imidazole framework structure ZIF-8 precursor comprises the following steps: Zinc nitrate hexahydrate and 2-methylimidazole are dissolved in methanol and mixed, stirred, allowed to stand, centrifuged, washed with methanol and vacuum dried to obtain a zeolite imidazole framework structure ZIF-8 precursor.
6. The method for preparing the composite material of elemental iron wrapped by acid-etched nitrogen-doped carbon nanotubes according to claim 4, characterized in that: In step (2), an iron source and a nitrogen source are added to the zeolite imidazole framework structure ZIF-8 precursor, specifically comprising: The zeolite imidazole framework structure ZIF-8 precursor obtained in step (1) is dissolved in ethanol, ferric chloride hexahydrate and dicyandiamide are added for ultrasonic treatment, and the mixture is collected by centrifugation and vacuum dried to obtain a solid mixture.
7. The method for preparing the composite material of elemental iron wrapped by acid-etched nitrogen-doped carbon nanotubes according to claim 4, characterized in that: In step (4), the acid is sulfuric acid, nitric acid or hydrochloric acid; The concentration of the acid is 0.1-1 mol / L; The mixing reaction time is 8 to 24 hours.
8. The method for preparing the composite material of elemental iron wrapped by acid-etched nitrogen-doped carbon nanotubes according to claim 4, characterized in that: In step (4), the post-processing specifically includes: Centrifuge first, then wash with ethanol and deionized water alternately until neutral, and then vacuum dry.
9. Acid-etched nitrogen-doped carbon nanotubes wrapped with elemental iron composite material is used in the air cathode system of microbial fuel cells, characterized in that: The acid-etched nitrogen-doped carbon nanotube-wrapped elemental iron composite material is prepared by the preparation method described in any one of claims 1 to 8.
10. The use according to claim 9, characterized in that: Specifically include: Acid-etched nitrogen-doped carbon nanotubes wrapped elemental iron composite material is loaded on a carbon cloth diffusion electrode as an oxygen reduction catalyst and used as the cathode of a microbial fuel cell. A relatively hydrophilic carbon cloth is used as a bioanode to construct an air cathode system for a microbial fuel cell.
Citation Information
Patent Citations
Oxygen evolution ferrocobalt-cobalt ferrite / nitrogen-doped nano-carbon tube composite catalyst and preparation method and application thereof
CN109524678A
Carbon nanotubes and preparation method thereof
CN109956463A
Fe-N-C catalyst with high catalytic activity as well as preparation method and application of Fe-N-C catalyst
CN114628695A
Iron-nitrogen double-doped carbon nano composite material and preparation method thereof
CN114824327A
Fuel cell electro-catalytic material and preparation method and application thereof
CN116130673A